Seed Storability and Genetic Parameters Estimation on Accelerated Aging Seed of Argomulyo Soybean (Glycine max (L.) Merr.) Mutant Lines - Siti MAESAROH; Yudiwanti WAHYU; Eny WIDAJATI (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
Seed storability of 22 selected soybean mutant lines from Argomulyo population irradiated by gamma ray were assessed by rapid aging tool, APC-IPB 77-1MM. Seed viability and vigor parameter observed due to genetic factors. The 90% ethanol was applied for 20, 40, 60 and 80 min as accelerated aging test. M100-96-53-6 was estimated that has good storability with less seed deterioration rate expressed by slow slope of germination percentage, germination speed and electrical resistance value after 20-80 min of chemical accelerated aging. Electrical resistance (ER) test could be as alternative and a substitute of electrical conductance (EC) test as alternative of vigor test. The high heritability and moderate to high genetic advance were noted on all parameters except moisture content. Germination percentage and germination speed could be reviewed for early stage selection to improve traits at the next generation based on R-square value of regresion and genetic parameters obtained.